(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2024)
This study focuses on the design of a photovoltaic system to supply electricity to the building "Block 5" of the FACI - UTLVTE. This design considers obtaining energy through two sources which are photovoltaic modules and the local power grid. Therefore, the designed photovoltaic system is conceived as an assisted solar photovoltaic installation. In the present research, calculations and simulations are carried out based on an analysis of the load demand and meteorological data obtained with PVsyst software. The results obtained indicate that the designed photovoltaic system can support a percentage of the demand of the lighting circuits, general outlets and special loads of Block 5, which corresponds to a decrease in the costs associated with the consumption of electricity from the local power grid. These results demonstrate that the sizing achieved by this photovoltaic system is optimal, which is validated by means of the PVsyst software.